Diagnóstico molecular e caracterização dos genes de virulência de infecção por Escherichia coli enteropatogênica em crianças no Semiárido Brasileiro - Santos, Ana Karolina Silva dos (2015)
The Escherichia coli diarrheagenic (DEC) are important pathogens associated with intestinal infections. Among these, Escherichia coli (EPEC) is one of the most important etiological agents for the diagnosis of diarrhea in infantos. However, the epidemiology of infections by these pathogens remain poorly elucidated in much of the world, so this study aimed to evaluate the impact of EPEC infection in children with and without diarrhea 2-36 months of life of the Brazilian semiarid, study type observational case-control, which also examined the presence or absence of diarrhea in children participating. The study population consisted of 365 cases and 365 controls, and the cases, children with diarrhea history in the 14 days before you check for the study. Socioeconomic parameters were evaluated through epidemiological questionnaire. The diagnosis of EPEC was carried out by xMAP (Bioplex 200) based on the eaeA genes (chromosomal) and bfpA (plasmid). Samples identified as EPEC were analyzed for five Polymerase Chain Reactions (PCR) of the Multiplex type for 19 EPEC virulence factors widely investigated in literature: espB, espD, tir, espC, espZ, espL, Ler, Map, espG, espH, nleE, nleF, nleB, paa, nleC, nleD, espJ, cesT and espP. Among the 730 children, EPEC was diagnosed in 118 children. The typical EPEC proved in 1.7% of cases (6/365) and 0.6% of controls (2/635). While atypical EPEC was detected in 13.7% of cases (50/365) and 16.4% of controls (60/365). And all samples isolated EPEC genes read, cest, and espB were the most prevalent (67.7%; 58.4%; 54.2% and 52.5%) respectively. These are associated with the global regulation of pathogenicity island bacteria, as well as the secretion and translocation various effector proteins into the host cell, and microtubule destruction and disruption tight junctions. In contrast, the lowest prevalence of the tir gene was (4,2% - 5/118), an important component of bacterial adhesion to host cell. The prevalence of the espD gene, associated with liposaccharide membrane pore translocation protein, was significantly associated with cases (p = 0.0354) as compared to controls. In the hierarchical combination analysis of the virulence genes the data suggest that three groups of genes were important and associated with the cases compared to the controls. The presence of the Paa gene, related to the protein associated with enterocyte adhesion injury, but in the absence of other virulence genes such as espH, espJ and espG, related to actin polymerization, inhibition of phagocytosis and effector translocation blocker T3SS , Respectively, are associated with cases compared to controls. A set of virulence genes, the presence of espJ and in the absence of nleF. And another set of virulence genes, with presence of espC, and in the absence of espP. The data also showed that in the hierarchical combinations of the virulence genes, such as the presence of espP and in the absence of nleF, as well as the presence of espG and in the absence of tir were associated with protection in the controls compared to the cases. The data suggest that the prevalence of EPEC is relatively high in this child population in the Brazilian semi-arid region.